2022
DOI: 10.3390/jfb14010008
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Dental Tissues Using Biomaterials with Piezoelectric Effect: Current Progress and Future Perspectives

Abstract: Dental caries and traumatic injuries to teeth may cause irreversible inflammation and eventual death of the dental pulp. Nevertheless, predictably, repair and regeneration of the dentin-pulp complex remain a formidable challenge. In recent years, smart multifunctional materials with antimicrobial, anti-inflammatory, and pro-regenerative properties have emerged as promising approaches to meet this critical clinical need. As a unique class of smart materials, piezoelectric materials have an unprecedented advanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 132 publications
0
8
0
Order By: Relevance
“…These piezoelectric biomaterials usually have highly ordered crystal lattices. When subjected to mechanical-stress-induced deformation, a relative shift of the positive and negative charge center within the material crystal structure occurs, resulting in motion of an electric dipole or polarization [ 233 ]. In simpler term, these materials can convert the mechanical stress from physiological activities into the electric current.…”
Section: Exogenous Electric Stimulationmentioning
confidence: 99%
“…These piezoelectric biomaterials usually have highly ordered crystal lattices. When subjected to mechanical-stress-induced deformation, a relative shift of the positive and negative charge center within the material crystal structure occurs, resulting in motion of an electric dipole or polarization [ 233 ]. In simpler term, these materials can convert the mechanical stress from physiological activities into the electric current.…”
Section: Exogenous Electric Stimulationmentioning
confidence: 99%
“…[296][297][298] Moreover, hydrogels with piezoelectric properties provide significant advantages due to their outstanding mechanical-to-electrical response, regulation of blood flow, and stimulation of angiogenesis. 299,300 Very recently, Ning and coworkers developed a piezoelectric hydrogel based on PAAN-PVDF for PIs or PUs (Fig. 8a-h).…”
Section: Polymers-based P-pegsmentioning
confidence: 99%
“…These EP further help to induce various steps of wound healing progression like proliferation and differentiation of fibroblasts, angiogenesis, collagen remodeling, etc. ( Figure 1B ) ( 17 ). For instance, a plethora of previous studies demonstrated that electric potential difference-derived electrical fields (EFs) generated from the piezo-potential to modulate skin cell behaviors ( 17 19 ).…”
Section: Introductionmentioning
confidence: 99%